PELATIHAN MANAJEMEN USAHA UNTUK UKM BATIK MALANGAN - Novi Nugrahani; Siti Amerieska; Andi Kusuma Indrawan; Ahmad Jarnuzi; Anik Kusmintarti (Jurnal Pengabdian kepada Masyarakat, 2021)
The purpose of this Community Service activity is to introduce the concept of Planet, People and Profit in business management management at UKM Batik Blimbing Malang. This Community Service Activity is carried out in the implementation of this activity divided into 2 (two) stages including a preliminary survey in the form of observations and interviews. From the results of observations and interviews. After that, the implementation was carried out on March 27, 2021. The activities were carried out using lecture and question and answer methods. UKM Batik Blimbing Malang has actually implemented the concept of Planet, People and Profit but has not yet known the terms in detail in the concept. The implementation of this PKM can help make it easier to introduce products by combining the uniqueness of batik and the 3P concept